Wear behaviour of stainless steel sintered and alloyed with titanium, cobalt and molybdenum - Korkut, Mehmet H. (My University, 2011)
Bu bilimsel makalede, titanyum, kobalt ve molibden ile alaşımlandırılmış ve sinterlenmiş paslanmaz çeliklerin aşınma davranışları incelenmiştir.

In this study, a powder mixture was prepared by adding 1–3 wt-% of FeMo, FeTi and Co powders to the austenitic stainless steel powders and samples were produced by the powder metallurgy method. Attempts were made to establish correlations between the microstructure, hardness, toughness, and abrasive wear values of these samples. Wear resistance of the materials was measured by a two body pin-on-disk wear tester. SiC abrasive papers of 65 mm and 177 mm sizes were used as the abrasive media. Wear tests were performed at the loads of 10, 20, and 30 N at room temperature. They showed that the softer, base austenitic stainless steel exhibited higher mass loss than the alloyed samples. Furthermore, the abrasive wear resistance of the base austenitic stainless steel composites increased with increasing FeTi, FeMo,Co content. The wear rate with the 177 mm SiC abrasive paper increased more than that with the 65 mm SiC abrasive paper.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Sintered; Powder Metallurgy; Wear; FeTi; FeMo; Austenitic Stainless Steels